2010
DOI: 10.1037/a0017447
|View full text |Cite
|
Sign up to set email alerts
|

Repetition blindness for rotated objects.

Abstract: Repetition blindness (RB) is the finding that observers often miss the repetition of an item within a rapid stream of words or objects. Recent studies have shown that RB for objects is largely unaffected by variations in viewpoint between the repeated items.In 5 experiments, we tested RB under different axes of rotation, with different types of stimuli (line drawings and shaded images, intact and split), using both novel and familiar objects. Although RB was largely viewpoint invariant, in most experiments, RB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
23
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 80 publications
8
23
1
Order By: Relevance
“…Thus, the pattern of results seen here may arise from a combination of RB mediated by scene gist and facilitation mediated by specific image features. This explanation would be consistent with a model proposed by Hayward et al (2010) in the context of RB for rotated objects. That study found RB for objects that were repeated in different orientations, but a reduction in the size of RB (sometimes even crossing into facilitation) when the objects were repeated in the identical orientation.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Thus, the pattern of results seen here may arise from a combination of RB mediated by scene gist and facilitation mediated by specific image features. This explanation would be consistent with a model proposed by Hayward et al (2010) in the context of RB for rotated objects. That study found RB for objects that were repeated in different orientations, but a reduction in the size of RB (sometimes even crossing into facilitation) when the objects were repeated in the identical orientation.…”
Section: Discussionsupporting
confidence: 91%
“…Repetition blindness has been demonstrated for a variety of stimuli, including letters, words, objects, and even novel 2-D and 3-D figures (Arnell & Jolicoeur, 1997;Bavelier & Potter, 1992;Coltheart, Mondy, & Coltheart, 2005;Harris & Dux, 2005a, 2005bHayward, Zhou, Man, & Harris, 2010;Kanwisher, 1987;Kanwisher & Potter, 1990;Kanwisher, Yin, & Wojciulik, 1999). It occurs for identical repetitions, but also for repetitions that are visually distinct, such as letters presented in different cases (Corballis & Armstrong, 2007;Kanwisher, 1987), orthographically similar words (Bavelier, Prasada, & Segui, 1994;Kanwisher & Potter, 1990) and objects presented in different orientations (Harris & Dux, 2005a, 2005bHayward et al, 2010).…”
Section: This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…1B) and were either attended or unattended. The half-split manipulation, while preserving the constituent object parts, distorted the holistic image in a way that cannot be recovered by the aligning processes of view-based models (Hayward et al, 2010;Thoma et al, 2004). To prevent verbalization of the attended object as a confounding factor we used a non-semantic attention task, in which participants detected brightness changes on either the object (attended condition) or a contralaterally presented noise stimulus (unattended condition).…”
Section: Introductionmentioning
confidence: 99%
“…Key to the configural change in these images is that the two halves of the image are swapped in location (as illustrated in Figure 1). This manipulation disrupts the 2D view of a familiar object while leaving the part-based description largely intact, and has been shown to distinguish between part-based and view-based representations (Hayward et al, 2010;Thoma et al, 2004). Splitting an image arguably presents an object in an unfamiliar view, but also crucially disrupts its holistic properties: In Biederman's (1987) Recognition-By-Components theory and Hummel's (2001) hybrid model, an object seen as a split 2D image is only recognisable from its component parts.…”
Section: Introductionmentioning
confidence: 99%